Effective/comparative investigation on green mediated nano copper oxide: Fabrication, characterization and environmental applications. (2022) - Prabha, I.; Nivetha, A.; Sakthivel, C.
Abstract: Nanomaterials are the leading edge for the rapid development of fascinating nanotechnology. The present work deals with the synthesis, structural and optical properties of Randia Dumetorum, sandalwood leaf extracts mediated copper oxide nanoparticles successfully. The synthesized nanomaterials were characterized by XRD for crystallite size and phase; SEM for morphology and particle size; UV–Vis for absorbance of the green synthesized copper oxide nanomaterials respectively. The crystallite size of the Randia Dumetorum and sandalwood mediated copper oxide nanomaterials were found to be 59.25 and 50.25 nm respectively. The synthesized nanomaterials have showed the morphology of spherical and clusters for Randia Dumetorum and sandalwood mediated copper oxide nanomaterials respectively. The copper oxide nanoparticle has acted as efficient catalyst for the oxidation of benzaldehyde. The benzoic acid obtained from chemical and green mediated catalyst was observed to be 3.89 and 4.25 g respectively.